Propozicija v funkcijski strukturi stavčne povedi - Vidovič-Muha, Ada (Slavistična revija, 2015)
Functional structure of a complete (clausal) sentence is two-part: it is based on the proposition as a lexical (dictionary) segment consisting of endogenous lexical items whose formal manifestation is-in accordance with their lexical nature-secondary (the denotation is at the forefront), and on modification as the grammatical segment. In that sense, the proposition may be understood as a nexus of the lexical meaning on the one side and of the potential meaning of a complete sentence on the other. - Derivational status of the predicative as a propositional component is controlled by the complex verb as a reflection of the complex predicator.
Keywords: besedne vrste; categorial grammatical attribute; categorial semantic component; complex verb; členek; free verbal morpheme; glagol; particle; povedkovnik; predicat; proposition; propozicija; skladnja; Slovene; Slovenian language; slovenščina; syntax; verb